The Role of Objects and Artifacts in Crafting the OnScreen Images of Mythological Medusa - Rojek, Patrycja (Przestrzenie Teorii, 2025)
Medusa, the Gorgon known for her monstrous appearance and petrifying gaze, is one of the most iconic figures in Greco-Roman mythology. Unlike many other mythological characters, Medusa can be identified solely by her distinctive physiognomy, without the need for symbolic attributes, as is often the case with depictions of deities. However, in the myth of Perseus, where Medusa is the main antagonist, various props play a crucial role in defining her character. This article explores the role of three key categories of these objects–those used against Medusa, those created by her gaze, andthose formed from her dead corpse–in shaping her image in film pop culture. Through an analysis of films such as Clash of the Titans (2010) and Percy Jackson & the Olympians: The Lightning Thief (2010), as well as their originals or remakes, the study demonstrates how these objects not only construct Medusa’s portrayal but also engage with themes of objectification and dehumanization.